Emotional intelligence: your success as a leader depends on it - Faronbi, Sunny (Henry Stewart Talks, 2020)
Leadership success, Emotional intelligence (EQ), Emotional Quotient (EQ), Reality testing, Introversion vs. Extroversion, Feeling vs. thinking